The role of gender in the use of Hungarian address forms - Domonkosi, Ágnes (Język. Komunikacja. Informacja, 2019)
Forms of address are directly related to the nature of social relationships. The gender of the discourse partners, including the question whether they are of the same or different genders, thus has an impact on the use of forms of address. The goal of this paper is to highlight the major gender-related characteristics of Hungarian address practices by reporting on a comprehensive sociolinguistic study based on questionnaires and interviews. In line with the perspective of social constructivism, the gender-related usage patterns of address forms are interpreted as actively shaping the construal of particular relationships and gender roles rather than merely reflecting them. Thus, the research findings suggest that iterative patterns in the use of more confidential/affectionate forms with women contribute to the maintenance of female gender roles.